One dragon two doves: a comparative history of the Catholic Church in China and in Vietnam - Leeb, Leopold (Studies in theology, society and culture, 2022)
"This comparative study of the history of the Catholic Church in China and Vietnam from the seventeenth to the twentieth century opens up new perspectives for the understanding of the presence of Christianity in Asia. The author narrates the biographies of a number of outstanding missionaries and Christians from China and Vietnam and tries to understand them in their respective historical backgrounds by applying the principle of mutual illumination: the experience of China may help to understand the Vietnamese reality and vice versa. In this way some interesting similarities between European missionaries and local Christians are revealed. At the same time the parallel biographies from China and Vietnam throw a light on the peculiar cultural and political contexts of Christianity in the two nations. The book, based on recent research in several languages, is a pioneering attempt at writing comparative ecclesiastical history in Asia and offers an insightful synopsis, occasionally even including observations on Japan and Korea. The study presents new questions and fields for further research, including native church leadership, Christian architecture, arts, and literature, and common theological vocabularies. The work discloses hitherto unnoticed spiritual links between China and Vietnam"--